2017
DOI: 10.1111/jpm.12350
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effect of coping styles on the association between psychological capital and psychological distress among Chinese nurses: a cross‐sectional study

Abstract: Introduction PsyCap includes four categories namely self-efficacy, hope, optimism and resilience. Research has demonstrated that PsyCap and coping styles affect current psychological distress. Nevertheless, few studies have explored the role of coping styles in PsyCap and psychological distress. Aim This study investigated the role of coping styles as a mediator in PsyCap and psychological distress among Chinese nurses. Methods Participants included 538 nurses who completed self-report questionnaires assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
71
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 42 publications
10
71
2
1
Order By: Relevance
“…Results from both correlation analysis and pathway analysis indicated that PsyCap had a negative correlation with distress, which provided evidence to accept hypothesis H2 (as PsyCap increases, distress of residents is expected to decrease). This relationship between distress and PsyCap was consistent with studies that illustrated the positive influence of PsyCap on distress in Chinese nurses and people living with HIV/AIDS who were employed full-time [55,56]. With multiple studies concluding that PsyCap is negatively correlated with distress, improving PsyCap of medical residents may act as a protective factor against the varying levels of distress that are experienced during residency.…”
Section: Discussionsupporting
confidence: 83%
“…Results from both correlation analysis and pathway analysis indicated that PsyCap had a negative correlation with distress, which provided evidence to accept hypothesis H2 (as PsyCap increases, distress of residents is expected to decrease). This relationship between distress and PsyCap was consistent with studies that illustrated the positive influence of PsyCap on distress in Chinese nurses and people living with HIV/AIDS who were employed full-time [55,56]. With multiple studies concluding that PsyCap is negatively correlated with distress, improving PsyCap of medical residents may act as a protective factor against the varying levels of distress that are experienced during residency.…”
Section: Discussionsupporting
confidence: 83%
“…Effective coping mechanisms require education and training programs. Those training programs might provide coping skills and social support for cyberbullying victims to alleviate distress [115].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is also important to clarify how these two coping strategies might reduce the negative effect of stressors on nurses´ mental health by mediating their relationship. Previous research has shown evidence of a partial mediating role of coping in the stress and health relationship (Klainin‐Yobas et al., 2014) and in the psychological capital and psychological distress relationship in Chinese nurses (Zhou et al., 2017). This mediation effect has, in some occasions, been shown differentiated for both types of coping (Noda et al., 2018).…”
Section: Introductionmentioning
confidence: 98%